Study of Various Method of Post Partum Infection Treatment on Dairy Cow - Prihatno, Surya Agus (Fakultas Kedokteran Hewan, Universitas Gadjah Mada, 2018)
Uterine infectious disease that occurs after partus on a cow is called metritis, or endometritis. Postpartum infections in dairy cows are common disease. The impact caused by metritis and endometritis is delayed of postpartum oestrus, high service per conception, and long calving interval. This disease causes economic losses for farmers. The purpose of this research is to determine the effective treatment methods of postpartum infections in dairy cows. 40 dairy cows 15 - 30 days postpartum, age 3 - 7 years devided into four groups, 10 cows in each group. First group was injected by prostaglandin 2α intramuscularly. Second group was injected by antibiotic oxytetracycline LA) intramusculary. Third group was treated by intrauterine infusion using cephapirin. Fourth group was injected with prostaglandin 2α intramuscularly combined with intra uterine infusion using povidone iodine. Postpartum oestrus was used as the recovering indicator. The research data was analized descriptively. The healing rate after treated with prostaglandin 2α, antibiotic (Oxytetrasicline), cephapirin, and combination of povidone iodine and prostaglandin 2α was 87.5%, 50%, 90% and 70% respectively, and the rate time of post partum oestrus occurrence was 99 days, 83 days, 80 days and 78 days respectively.